Liver laceration and hemoperitoneum in a premature neonate: a rare case of perinatal trauma - Joana Marques; Olga Voutsen; Sérgio Ferreira; Rosalina Barroso (Hygeia Press di Corridori Marinella, 2021)
We present a case of a premature very low birth weight neonate who developed abdominal distension and acute anemia on his 2nd day of life, in which a liver laceration was diagnosed. Neonatal hepatic injury is rare but frequently fatal. It usually happens due to perinatal trauma in complicated labor or delivery or when resuscitation maneuvers take place. It can result in a subcapsular hematoma of the liver but can also translate as a simple laceration. When the hepatic capsule ruptures, a hemoperitoneum usually develops. Umbilical vein catheterization, hepatic congestion and an increased bleeding tendency have also been associated with liver injury and hemorrhaging in the neonate. Clinical presentation can vary from abdominal distension to acute anemia or even hemorrhagic shock. Unspecific signs such as lethargy, tachypnea, feeding intolerance, jaundice and laboratory findings of thrombocytopenia, coagulation disturbances and hyperbilirubinemia can occur. Diagnosis may be difficult, and imaging methods are essential. A conservative approach to treatment is usually preferred, even in the case of a hemoperitoneum. In the case described, there was a history of a difficult extraction and need for resuscitation maneuvers at birth. The abdominal radiograph showed a large liver, and ultrasound revealed a hepatic laceration and a hemoperitoneum. Treatment was supportive, consisting of blood components, expectant observation and strict avoidance of abdominal manipulation. Follow-up of the lesion through serial ultrasounds was performed, and the infant survived, recovering well. This case is one of the few in recent literature describing a good outcome in neonatal liver injury. Awareness of the possibility of its occurrence is important, especially in premature neonates, who are at particular risk.